Krameria lappacea roots extract to rescue coccidiosis-mediated inflammation in the jejunum of C57BL/6 mice - Abdel-Gaber, Rewaida; Alamari, Ghada; Dkhil, Mohamed A.; El-Ashram, Saeed; Al-Hoshani, Nawal; Al-Shaebi, Esam M.; Al-Quraishy, Saleh (Frontiers in Immunology, 2025)
IntroductionCoccidiosis is a protozoan disease caused by Eimeria species, which multiply in the intestinal tract and lead to severe inflammatory responses. While coccidiostats are available for control, resistance to these treatments has been confirmed, underscoring the need for new eco-friendly approaches. In recent years, natural plant sources have gained attention as effective alternatives for treating various parasitic diseases. Krameria lappacea has been used in traditional medicine due to its pharmacological properties. This study examined the effects of the aqueous methanolic extract of K. lappacea roots (KLRE) on jejunal inflammation and immune response in a murine model infected with Eimeria papillata.MethodsTwenty-five male C57BL/6 mice were randomly divided into five groups. The first group received only distilled water, while the second group was administered 200 mg/kg of KLRE for 5 days. The third, fourth, and fifth groups were orally injected with 103 sporulated oocysts of the Eimeria parasite. For treatment, the fourth group received KLRE (200 mg/kg), and the fifth group received amprolium (120 mg/kg) orally for 5 days. All mice were euthanized on day 5 post-infection (p.i.), and blood samples and jejunum were collected. Investigations were conducted to assess oocyst shedding, cellular immune response, and the histological changes in the jejunum of the mice. Levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α were measured using an enzyme-linked immunosorbent assay (ELISA). Additionally, the mRNA expression of CXC motif chemokine ligand 10 (CXCL10), interferon-inducible gene 202b (IFi202b), and secreted phosphoprotein 1 (SPP-1) was analyzed using quantitative reverse transcription polymerase chain reaction (qRT-PCR).ResultsOur study demonstrated that mice infected with E. papillata produced an average of 5.387 × 106 ± 4.29 × 105 oocysts per gram of feces by day 5 post-infection. In contrast, the output was significantly reduced to 1.308 × 106 ± 1.36 × 105 oocysts per gram of feces in mice treated with KLRE. These findings suggest that the host immune response to the intracellular Eimeria parasite triggers inflammation and injury in the jejunum of the mice. This was evidenced by several factors: (i) an elevated inflammatory histological score, (ii) an increased cellular immune response characterized by neutrophils and lymphocytes, (iii) elevated protein levels of IL-1β, IL-6, and TNF-α, measured at approximately 13.67 ± 2.07, 78.98 ± 4.17, and 222.28 ± 10.18 pg/ml, respectively, and (iv) upregulated expression of the mRNA genes CXCL10, IFi202b, and SPP-1, which showed fold changes of approximately 2.83, 3.55, and 3.07-fold, respectively. Our study found that all parameters associated with the infection were significantly altered during treatment with KLRE.ConclusionOur data showed that KLRE treatment significantly reduced inflammation and histological damage in the jejunum caused by E. papillata infections.